2021
DOI: 10.37496/rbz5020200166
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of polyherbal with vitamin C activity on lamb performance and meat characteristics

Abstract: We conducted an experiment to evaluate the effect of a polyherbal additive with metabolites such as antioxidants, vitamins, and small hydrolysable tannoids oils on productive parameters and blood metabolites in finishing lambs. Forty male Hampshire × Suffolk lambs (23.79±2.24 kg) were used in a completely randomized experimental design. Treatments consisted of dietary inclusion of a polyherbal additive based on Emblica officinalis and Ocimum sanctum at 0, 5, 10, and 15 g/kg dry matter for 60 d. There were no e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 35 publications
(52 reference statements)
3
7
0
Order By: Relevance
“…However, in this study, no significant changes in DMI were observed in response to dietary PA supplementation. Similar results were previously reported by Lozano-Sánchez et al [ 23 ] in lambs supplemented with a PA (0, 5, 10, and 15 g kg −1 DM for 60 days) based on Emblica officinalis and Ocinum sanctum containing hydrolyzable tannins and by Orzuna-Orzuna et al [ 6 ] in finishing lambs supplemented with PA (0, 1, 2 and 3 g kg −1 DM for 56 days) containing saponins, flavonoids, and polysaccharides. On the other hand, Hashemzadeh et al [ 3 ] observed 18% higher DMI in lambs supplemented with a PA (20 g kg −1 DM for 48 days) based on Rosemarinus offıcinalis , Cinnamomum zeylanicum , Curcuma longa, and Eugenia caryophyllata .…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…However, in this study, no significant changes in DMI were observed in response to dietary PA supplementation. Similar results were previously reported by Lozano-Sánchez et al [ 23 ] in lambs supplemented with a PA (0, 5, 10, and 15 g kg −1 DM for 60 days) based on Emblica officinalis and Ocinum sanctum containing hydrolyzable tannins and by Orzuna-Orzuna et al [ 6 ] in finishing lambs supplemented with PA (0, 1, 2 and 3 g kg −1 DM for 56 days) containing saponins, flavonoids, and polysaccharides. On the other hand, Hashemzadeh et al [ 3 ] observed 18% higher DMI in lambs supplemented with a PA (20 g kg −1 DM for 48 days) based on Rosemarinus offıcinalis , Cinnamomum zeylanicum , Curcuma longa, and Eugenia caryophyllata .…”
Section: Discussionsupporting
confidence: 90%
“…Although it has previously been reported that dietary supplementation of tannin-containing plants can increase HCY and CCY [ 11 ], in this study HCW, HCY, CCW, CCY, ELC, ILC, CG, LL, and CI were similar in lambs of the different treatments. Similar responses were previously reported by Orzuna-Orzuna et al [ 5 ] in lambs supplemented with increasing doses (0, 1, 2, and 3 g kg −1 DM for 56 days) of a PA containing flavonoids, essential oils, and alkaloids; and by Lozano-Sánchez et al [ 23 ] in lambs supplemented with a PA (0, 5, 10, and 15 g kg −1 DM for 60 days) containing 12% hydrolyzable tannins.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In a study performed on buffalo calves, phytogenic additives containing amla fruit enhanced immune status, and increased metabolite concentrations in the blood, such as total protein, albumin, globulin, aspartate transaminase, and alanine transaminase [29,30]. According to Lozano-Sánchez et al [31], the herbal additive that contains amla fruits does not affect metabolites (glucose, urea, cholesterol) related to energy or protein metabolism. Moreover, amla fruit extract with other polyherbal ingredients can improve immunity and udder health in cows [32].…”
Section: Introductionmentioning
confidence: 99%